Knowledge, Skills, and Attitudes of Recent Medical Graduates Regarding the Management of Poisoning Cases - Saima Manzoor; Zubia Iqbal; Maria Safdar; Nasir Abbas; Amna Zafar; Muhammad Asif (Pakistan Journal of Health Sciences, 2026)
Poisoning remains a major cause of emergency department visits and preventable mortality, particularly in low- and middle-income countries. Newly graduated medical officers are frequently the first responders in poisoning emergencies. Objectives: To evaluate the knowledge, skills, and attitudes of recent medical graduates regarding the diagnosis, management, and medico-legal responsibilities associated with poisoning cases. Methods: An analytical cross-sectional study was conducted among 201 recent MBBS graduates working in tertiary care teaching hospitals in Lahore, Pakistan. A structured, pilot-tested questionnaire assessed knowledge using multiple-choice and scenario-based questions, skills through structured clinical scenarios, and attitudes using Likert-scale items. Data were analyzed using SPSS version 26.0. Independent t-tests, chi-square tests, Pearson correlation, and multiple linear regression were applied. A p-value ≤0.050 was considered statistically significant. Results: Graduates who completed an emergency department rotation demonstrated significantly higher knowledge scores than those without such training. Greater exposure to poisoning cases was associated with improved practical skills, and a moderate positive correlation was observed between the number of poisoning cases managed and overall competence. Emergency rotation and clinical exposure independently predicted competence after adjustment for demographic variables. Major competence gaps were identified in toxidrome recognition, decontamination sequencing, airway protection, corrosive poisoning management, and medico-legal documentation. Conclusions: Recent medical graduates possess moderate theoretical knowledge but demonstrate important deficiencies in practical and medico-legal competencies. Structured emergency rotations and simulation-based toxicology training are essential to improve preparedness for poisoning management.